Childhood Vaccine Hesitancy in selected Islamic and Muslim-majority Countries : Result Synthesis from a Scoping Review - Samsudin, Khalsom; Abdul Manaf, Rosliza; Mahmud, Aidalina (IIUM Medical Journal Malaysia, 2023)
Vaccine hesitancy and refusal were linked to various religious beliefs, including Islam. Regardless, there were limited studies which offer insights into the role of religious affiliations and related misconceptions in childhood vaccination refusal and hesitancy in Islamic and Muslim Majority countries (MMC). Therefore, this review identifies the prevalence of childhood vaccine hesitancy and its contributory factors while determining the role of religious beliefs in childhood vaccine hesitancy in Islamic states and MMC. We examined four electronic databases for published studies related to childhood vaccine hesitancy and refusal in Islamic countries or MMC from 2011 to 2021. Results revealed that the prevalence of vaccine hesitancy and vaccine refusal range from 8.0% to 21.0% and 1.0% to 58%, respectively, which was comparable to other countries. Parental reasons contributing towards vaccine hesitancy and refusal include concerns related to vaccine safety, side effects and effectiveness, preference for alternative measure to prevent disease, prior bad experiences, and healthcare system distrust. Religious reasons instigating vaccine hesitancy include concerns that vaccine consists of haram ingredients, beliefs that vaccine is against God’s will, perceptions of vaccine being harmful, influences from religious leaders, and distrust towards religious authorities supporting vaccination. In brief, various factors induce vaccine hesitancy and refusal in Islamic states and MMC. Further studies could provide better insights into the role of religious factors in childhood vaccine hesitancy within local contexts in order to formulate effective interventions to address this issue.